2011
DOI: 10.4161/psb.6.12.18050
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction affects chloroplast functions

Abstract: Plants require the contribution of three different genomes found in separate compartments. Chloroplasts and mitochondria, which are of endosymbiotic origin, contain only relatively few proteins encoded by their own genomes, following the transfer of a great part of the genetic material from the prokaryotic ancestors into the nucleus of the host. Consequently, most of the mitochondrial and chloroplast proteins are nuclear-encoded, synthesized in the cytoplasm and imported into organelles. [1][2][3] Given that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Various works have shown that the mitochondria have a key role in the provision of cellular energy, as well as in the participation in retrograde regulation mechanisms involved in the biogenesis of other organelles ( i.e. , chloroplasts) in plants and algae ( Busi et al, 2011 ; Liu & Butow, 2006 ; Liu et al, 2018 ). Although mitochondria and chloroplasts were traditionally considered as autonomous compartments, there is much evidence that the crosstalk between these organelles directly impacts on cell physiology ( Raghavendra & Padmasree, 2003 ).…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Various works have shown that the mitochondria have a key role in the provision of cellular energy, as well as in the participation in retrograde regulation mechanisms involved in the biogenesis of other organelles ( i.e. , chloroplasts) in plants and algae ( Busi et al, 2011 ; Liu & Butow, 2006 ; Liu et al, 2018 ). Although mitochondria and chloroplasts were traditionally considered as autonomous compartments, there is much evidence that the crosstalk between these organelles directly impacts on cell physiology ( Raghavendra & Padmasree, 2003 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Although mitochondria and chloroplasts were traditionally considered as autonomous compartments, there is much evidence that the crosstalk between these organelles directly impacts on cell physiology ( Raghavendra & Padmasree, 2003 ). For example, mitochondrial metabolism, particularly the bioenergetic reactions of oxidative electron transport and phosphorylation are still active in the light and are essential for maintain photosynthetic carbon assimilation ( Busi et al, 2011 ; Raghavendra & Padmasree, 2003 ).…”
Section: Survey Methodologymentioning
confidence: 99%